Are children driving the gender wage gap? Comparative evidence from Poland and Hungary - Ewa Cukrowska; Anna Lovász (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2014)
We examine how much children and responsibilities related with them contribute towards the divergence of mens and womens wages, and consequently, to the formation of the gender wage gap. To derive the relative contribution of gender specific wage inequalities caused by the parenthood to the overall gender wage gap, we provide a modification of standard Oaxaca-Blinder decomposition method, and correct simultaneously for selection into work and parenthood. Contrary to our expectations, the findings show that most of the gender wage inequality is due to the positive wage gap between men who do and do not have children and not due to the wage penalty incurred by mothers.
Keywords: J13; J22; 330; Gender Wage Gap; Family Gap; Motherhood Penalty; Wage Gap Decomposition